Effect of process parameters on lipase production by Candida cylindracea in stirred tank bioreactor using renewable palm oil mill effluent based medium - Salihu, Aliyu; Alam, Md Zahangir; AbdulKarim, M. Ismail; Mohd. Salleh, Hamzah (Elsevier B.V., 2011)
A two-level full factorial design (FFD) was employed to determine the effects of process parameters on lipase production by Candida cylindracea ATCC 14830 in palm oil mill effluent (POME)-based medium. Ten experimental runs based on three parameters (temperature, agitation and aeration) as indicated by the FFD were carried out in a stirred-tank bioreactor. On statistical analysis of the results, the optimum temperature, aeration and agitation rates were found to be 30 ◦C, 1.0 vvm and 400 rpm respectively, with a maximum activity of 41.46 U/ml after 36 h of fermentation. Analysis of variance (ANOVA) showed a high coefficient of determination (R2) value of 0.999, indicating a satisfactory fit of the model with the experimental data. All the three parameters were statistically significant at p < 0.05. The validation experiment also confirmed that apart from lipase production, there was an increase in chemical oxygen demand (COD) removal throughout the fermentation period.